Sexual dimorphic impact of adult‐onset somatopause on life span and age‐induced osteoarthritis. Issue 8 (9th July 2021) - Poudel, Sher Bahadur; Dixit, Manisha; Yildirim, Gozde; Cordoba‐Chacon, Jose; Gahete, Manuel D.; Yuji, Ikeno; Kirsch, Thorsten; Kineman, Rhonda D.; Yakar, Shoshana
Abstract: Osteoarthritis (OA), the most prevalent joint disease, is a major cause of disability worldwide. Growth hormone (GH) has been suggested to play significant roles in maintaining articular chondrocyte function and ultimately articular cartilage (AC) homeostasis. In humans, the age‐associated decline in GH levels was hypothesized to play a role in the etiology of OA. We studied the impact of adult‐onset isolated GH deficiency (AOiGHD) on the life span and skeletal integrity including the AC, in 23‐ to 30‐month‐old male and female mice on C57/BL6 genetic background. Reductions in GH during adulthood were associated with extended life span and reductions in body temperature in female mice only. However, end‐of‐life pathology revealed high levels of lymphomas in both sexes, independent of GH status. Skeletal characterization revealed increases in OA severity in AOiGHD mice, evidenced by AC degradation in both femur and tibia, and significantly increased osteophyte formation in AOiGHD females. AOiGHD males showed significant increases in the thickness of the synovial lining cell layer that was associated with increased markers of inflammation (IL‐6, iNOS). Furthermore, male AOiGHD showed significant increases in matrix metalloproteinase‐13 (MMP‐13), p16, and β‐galactosidase immunoreactivity in the AC as compared to controls, indicating increased cell senescence. In conclusion, while the life span of AOiGHD females increased, their health span was compromised by high‐grade lymphomas and the development of severe OA. In contrast, AOiGHD males, which did not show extended life span, showed an overall low grade of lymphomas but exhibited significantly decreased health span, evidenced by increased OA severity. Abstract : In humans, the natural decline in growth hormone (GH) secretion during aging, termed somatopause, associates with reduced health span. We found that age‐induced somatopause in mice increased primary osteoarthritis (OA) of the knee joint. This was evidenced by the loss of articular cartilage, increased osteophyte formation, and thickening of the synovial membrane. At the cellular level, somatopause increased chondrocyte expression of matrix‐degrading enzymes, senescence, and inflammatory markers.